X-ray fluorescence spectrometry: An alternative technique for analysis of waste - Marcos Antonio Scapin; Maria Cristina Tessari-Zampieri; Sabine Guilhen; Marycel Cotrim (Brazilian Journal of Radiation Sciences)
This study aims to develop reliable analytical methodology that is, cost-effective, and requires minimal sample quantity to quantify uranium content in nuclear waste and others. The Energy Dispersive X-ray Fluorescence Spectrometry (EDXRF) technique was used, and a rigorous comparison was made between the fundamental parameters (FP) method and the empirical (EMP) method. Statistical evaluation of results demonstrated that the FP method showed a satisfactory level of confidence for precision and limit of quantification.